KEMAMPUAN MATHEMATICAL CREATIVE PROBLEM SOLVING, BERPIKIR KRITIS MATEMATIS, DAN SELF EFFICACY SISWA SMP DALAM IMPLEMENTASI EXPERIENTIAL LEARNING MODEL - Anik Yuliani, - (2022)
The main objective of this research is to examine the achievement and enhancement of mathematical creative problem-solving abilities (MCPS) and mathematical critical thinking abilities (BKM) as well as the achievement of self-efficacy (SE) in terms of initial mathematical abilities (high, medium and low), as a result of the implementation of experiential learning and dirrect instruction. This research is based on the importance of mathematical creative problem-solving abilities (MCPS), mathematical critical thinking abilities (BKM) and self-efficacy (SE) in junior high school students, but in reality there are still many studies that find mathematical creative problem-solving abilities (MCPS) and mathematical critical thinking abilities (BKM) as well as students' self-efficacy (SE) are still low. The research method used is quasi-experimental with the non-equivalent control design. The population in this study were all students in one of the State Junior High School students in Cimahi City in 2019. The sample was class VIII students at the selected State Junior High School. Two classes were randomly selected from the six classes in the selected State Junior High School, one as the experimental group and the other as the control group. The experimental group was given experiential learning and the control group was given dirrect instruction. The instruments used in this study consist of a prior mathematical knowledge test (PMK), a mathematical creative problem-solving abilities test, a mathematical critical thinking abilities test, and a self-efficacy scale. The results of data analysis used t-test, -test, Mann-Whitney test, two-way Anova test, and Pearson Chi-square test. The results show that (1) there are differences in the achievement and enhancement of mathematical creative problem solving abilities and mathematical critical thinking abilities between the students who received experiential learning and the students who received dirrect instruction, both in terms of learning factors and from the PMK level (high, medium, low); (2) there are differences in the achievement of self-efficacy between the students who received experiential learning and students who received dirrect instruction, both in terms of learning factors and PMK levels (high, medium, low); (3) there is no interaction effect of learning factors and PMK level on the achievement and enhancement of mathematical creative problem solving abilities and mathematical critical thinking skills as well as on the achievement of students' self-efficacy; (4) there is a very strong correlation between the students' mathematical creative problem solving abilities and mathematical critical thinking abilitie in experiential learning classroom; (5) there is a strong correlation between mathematical the students' creative problem solving abilities and self-efficacy in experiential learning classroom; and (6) there is a strong correlation between the students' mathematical critical thinking abilities and self-efficacy in experiential learning classroom.